Long-term effects of a mandatory multistage program: The new deal for young people in the UK - Giacomo De Giorgi (Institute for Fiscal Studies (IFS), 2005)
The New Deal For Young People is the major welfare-to-work program in the UK. It is a mandatory multistage policy targeted at the 18-24 year old unemployed. This paper investigates the effectiveness of the program in terms of enhancing the (re)employment probability of participant males. I exploit the eligibility rule to identify a suitable counterfactual relying upon a simple regression discontinuity design. By exploiting such a discontinuity I am able to non parametrically identify (Hahn et al., 2001) a local average treatment effect (LATE). While relying upon the non parametric local linear regression method I am able to push forward such a parameter to a global dimension, implicitly adding parametric structure. No evidence of possible general equilibrium as well as substitution effects is found by a co- hort specific approach (before and after the program). The main result is that the program enhances employability by about 6-7%.
Keywords: J18; J23; J38; C14; 330; Labour market policy evaluation; regression discontinuity; non parametric; Aktivierende Sozialhilfe; Absolventen; Projektbewertung; Großbritannien; Junge Arbeitskräfte; Berufseinstieg